Heat transfer enhancement by recirculating flow within liquid plugs in microchannels - Che, Zhizhao (2012)
Plug flow can significantly enhance heat transfer in microchannels as compared to single phase flow. Using an analytical model of flow field, heat transfer in plug flow is investigated. The constant-surface-temperature boundary condition is considered. Three stages of the heat transfer in plugs are identified: (i) development of thermal boundary layer; (ii) advection of heated/fresh fluid in the plug; and (iii) thermally fully developed flow. Due to the transport of heated fluid and fresh fluid within the plug by the recirculating flow, oscillations of the Nusselt number at high Peclet numbers are observed and explained. The effects of the Peclet number and the plug length on the heat transfer process are evaluated. The results show that short plugs are preferable to long plugs since short plugs result in high Nusselt numbers and high heat transfer indices.